Monitoring system of electrodynamic braking of DC electric train with collector traction motors - V. A. Baranov; I. P. Vikulov; A. A. Kiselev; A. S. Maznev (Вестник Научно-исследовательского института железнодорожного транспорта)
High proportion of electric trains with collector trac-A monitoring system of electrodynamic braking has been develotion motors in the multiple unit fleet and its low cost in comparison ped with preservation of the electric train standard equipment. It al-with electric trains with an asynchronous traction make it neces-lows regulating the recuperative current depending on the possibility sary to improve the control system of motor collectors. One of the of its consumption by changing the resistance of the braking resistors. ways is to create devices to improve the efficiency of recuperative Imitation model of DC electric train power circuit in the electrobraking. dynamic braking mode with a monitoring system was developed.It takes into account the influence of eddy currents in the motor frame, armature current ripples and the catenary voltage increase during recuperative braking.Electromagnetic processes in the electric train power circuit are investigated. Analysis of the obtained oscillograms shows the change in the armature current and the catenary voltage within the specified limits in the braking mode. Recuperative current regulator is tuned to an aperiodic transient with a time equal to 0.015 s.The paper shows possibility of the monitoring system to regulate the armature current in the recuperative mode together with the automatic braking control system in case of increasing the catenary voltage. When the voltage fails, the monitoring system is not able to limit the increasing braking current, its reduction is effected by the magnetic flux of the traction motors.Adjusting characteristic and the technical effect from the implementation of the monitoring system are calculated. The possibility of reducing the electric power consumption by 4.62 % is shown.